2023
DOI: 10.3389/fpsyt.2023.1138389
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms in Long-COVID patients: a systematic review

Mattia Marchi,
Pietro Grenzi,
Valentina Serafini
et al.

Abstract: ObjectivePeople who have been infected by COVID-19 showing persistent symptoms after 4 weeks from recovery are thought to suffer from Long-COVID syndrome (LC). There is uncertainty on the clinical manifestations of LC. We undertook a systematic review to summarize the available evidence about the main psychiatric manifestations of LC.MethodPubMed (Medline), Scopus, CINHAL, PsycINFO, and EMBASE were searched until May 2022. Studies reporting estimation of emerging psychiatric symptoms and/or psychiatric diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 65 publications
1
6
1
Order By: Relevance
“…The minimal or absent impact of merely contracting the infection on physical and mental health and cognitive performance, which contrasts with results of many already published studies, e.g. (Altuna, Sánchez-Saudinós, Lleó, & 2021; Delgado-Alonso et al, 2022; Flegr & Latifi, 2023; Havervall et al, 2021; Lamontagne et al, 2021; Lu et al, 2020; Marchi et al, 2023; Mazza et al, 2020; O’Mahoney et al, 2023; Zhao et al, 2020) could be related to the fact that all students included in our study were younger than 31 years old (95% were 20-24 years old). As is often the case with such a young population, most students experienced a relatively mild form of COVID-19; only about 20% described it as “severe flu,” and none of the study participants was hospitalized due to COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
“…The minimal or absent impact of merely contracting the infection on physical and mental health and cognitive performance, which contrasts with results of many already published studies, e.g. (Altuna, Sánchez-Saudinós, Lleó, & 2021; Delgado-Alonso et al, 2022; Flegr & Latifi, 2023; Havervall et al, 2021; Lamontagne et al, 2021; Lu et al, 2020; Marchi et al, 2023; Mazza et al, 2020; O’Mahoney et al, 2023; Zhao et al, 2020) could be related to the fact that all students included in our study were younger than 31 years old (95% were 20-24 years old). As is often the case with such a young population, most students experienced a relatively mild form of COVID-19; only about 20% described it as “severe flu,” and none of the study participants was hospitalized due to COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
“…Mental and physical aspects of HRQoL were significantly reduced in COVID-19 patients 6 months after discharge. A reduced mental aspect of HRQoL is consistent with the findings of sleep disturbances, depression, anxiety, and cognitive impairment as reported in a systematic review ( 28 ). Of note, the comparison of HRQoL scores was adjusted by age and sex according to national normative data, which strengthens the evidence for this impairment when compared to the general population.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings align with a metaanalysis of 33 studies that reported a 19% prevalence of PTSD and 21% prevalence of depression after the COVID-19 illness. 10 We also examined which individual cognitive domains were particularly affected after COVID-19 to fully characterize the oftreported "brain fog." We observed prominent impairments in executive function and immediate and delayed memory-domains previously reported to be affected by critical illness and acute respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another meta-analysis reported that 19% developed post-traumatic stress disorder (PTSD) and 21% developed depression. 10 To our knowledge, few studies have evaluated modifiable risk factors during hospitalization, such as delirium, medications, and the effect of in-person and virtual visitation with friends and family on the severity of Long-COVID symptoms. Identifying in-hospital modifiable risk factors could assist with the development of strategies to prevent or lessen the contribution of neuropsychological dysfunction to Long-COVID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation